Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T01:04:09+02:00
59
W(x)=ax(x+b)²
V(x)=x³+2x²+x

W(x)=ax(x+b)²=ax(x²+2xb+b²)=ax³+2x²ab+ab²x

ax³+2x²ab+ab²x=x³+2x²+x

porównujemy współczynniki (liczby) przy tych samych potęgach x

zatem:
a=1 przy x³
2ab=2 więc 2b=2 to b=1
ab²=1 pasuje

czyli: a=b=1

60

3/(x-3)-x/(x+1)=

3(x+1)/(x-3)(x+1)-x(x-3)/(x+1)(x-3)=

[3(x+1) -x(x-3)]/(x+1)(x-3)=

[3x+3 -x²+3x)]/(x²-3x+x-3)=

[3 -x²+6x)]/(x²-2x-3)

61
2x-y-11=0
punkt P=(1;2)

2x-y-11=0
y=2x-11
równoległa wiec a=2

y=2x+b
podstawiamy współ. punktu P
2=2*1+b
2=2+b
b=0

prosta: y=2x